Interventions supporting the translation of gerontological evidence into practice to optimize functional outcomes for hospitalized older adults: A scoping review. - Kathleen F Hunter; Jeffrey I Butler; Shovana Shrestha; C Allyson Jones; Adrian Wagg; Nick Millar; Frances Carr; Sherry Dahlke (PLoS ONE)
Background and objectives Hospitalized older adults are at risk for both physical and cognitive functional decline. To support the implementation of interventions optimizing their function, both healthcare professional knowledge and other factors that may impact practice change should be addressed. The objective of this study was to examine the characteristics and type of interventions supporting the translation of gerontological evidence into practice to optimize functional outcomes for hospitalized older adults. Materials and methods This scoping review used the guidelines recommended by Peters et al. Six electronic databases were searched from database inception to 2024. Included studies were primary research studies that 1) described an educational intervention for healthcare professionals as part of an initiative to promote practice change and 2) assessed functional outcomes (physical and/or cognitive). Results Thirty-eight studies were deemed eligible. Numerous interventions to support implementation of knowledge to improve functional outcomes were identified. In addition to educational strategies, other interventions addressed care processes, changes to the built environment, administration/management support, leadership support/facilitation, and discharge/transition planning. Studies employed a range of measures to assess functional outcomes among hospitalized older adults. Discussion Older studies tended to focus on nurse-driven interventions, and newer ones on interprofessional interventions. Knowledge gaps were highlighted in terms of theory, research designs, intervention descriptions, country representation, policy, environmental changes, and leadership roles. Future evaluations of interventions to enhance older adults' functioning should examine effectiveness and compare single- and multi-intervention programs. Strategies based on implementation science theory are needed to ensure successful uptake of effective interventions, while also addressing real-world issues in hospital units, such as short staffing, resource constraints, and overcrowding.